Investigating Mediation Effect of Innovation on the Relationship Between Project Management and Property Organizational Performance - Alhamed, Mohsen Mohamed; Wan Yusoff, Wan Fauziah (International Journal of Sustainable Construction Engineering and Technology, 2023)
In the context of challenging property organizational performance, innovation plays a crucial role in mediating the relationship between project management and organizational performance. Therefore, this paper presents a study aiming to develop and assess a mediation model where project management acts as the independent variable, innovation as the mediator, and property organizational performance as the dependent variable. Data were collected through a questionnaire survey among employees in real estate companies in the UAE, distributing 390 questionnaires using traditional random sampling techniques. However, the model utilized responses from 375 completed questionnaires. The collected data were employed to develop the model in SmartPLS software, which was then analysed and assessed at both the measurement and structural components. The findings indicate that all direct relationships are statistically significant, except for one: QTY -> INNO. Concerning indirect relationships, two out of the four relationships are not statistically significant: QTY -> INNO -> PFM and SCP -> INNO -> PFM. Additionally, the mediator variable, INNO, induces two instances of partial mediation and two instances without any mediation effect. Moreover, the model’s Goodness-of-Fit value is 0.766, indicating that the model has 76.6% of predictive capability.